2007
DOI: 10.1037/1099-9809.13.1.64
|View full text |Cite
|
Sign up to set email alerts
|

Racism experiences and psychological functioning in African American college freshmen: Is racial socialization a buffer?

Abstract: Previous research has documented the negative effects of racism on the psychological health of African Americans. However, consideration of racial socialization as a potential buffer against racism experiences has received limited attention. The present study investigated whether two types of parental racial socialization messages reduced the impact of racism on psychological functioning in a sample of 247 African American college freshmen (M=18.30). Results indicated that students who reported more racism exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
145
1
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(156 citation statements)
references
References 43 publications
7
145
1
3
Order By: Relevance
“…Contrary to previous research, which has identified family as the primary source of racial socialization messages to inform individuals about cultural history and values, prepare them for potential experiences of prejudice in regards to race, and provide guidance for coping with discrimination (Brody et al, 2006;Bynum et al, 2007;Fischer & Shaw, 1999;Gillem, Cohn, & Throne, 2001;Hughes et al, 2006;Kerwin et al, 1993;Kerwin & Ponterotto, 1995;McClain DaCosta, 2004;Miville et al, 2005;O'Brien Caughy, 2004;Phillips Smith, & Johnson, 2009;Robbins et al, 2007;Rodriguez, Umaña-Taylor, Smalls, 2010;Root, 1998;Stevenson & Renard, 1993;White-Johnson et al, 2010;Wills et al, 2007), only five of the 12 participants reported that issues of race were directly addressed within their families. As such, it appeared that racial socialization messages were received more implicitly across different contexts in their lives.…”
Section: Researchmentioning
confidence: 66%
See 1 more Smart Citation
“…Contrary to previous research, which has identified family as the primary source of racial socialization messages to inform individuals about cultural history and values, prepare them for potential experiences of prejudice in regards to race, and provide guidance for coping with discrimination (Brody et al, 2006;Bynum et al, 2007;Fischer & Shaw, 1999;Gillem, Cohn, & Throne, 2001;Hughes et al, 2006;Kerwin et al, 1993;Kerwin & Ponterotto, 1995;McClain DaCosta, 2004;Miville et al, 2005;O'Brien Caughy, 2004;Phillips Smith, & Johnson, 2009;Robbins et al, 2007;Rodriguez, Umaña-Taylor, Smalls, 2010;Root, 1998;Stevenson & Renard, 1993;White-Johnson et al, 2010;Wills et al, 2007), only five of the 12 participants reported that issues of race were directly addressed within their families. As such, it appeared that racial socialization messages were received more implicitly across different contexts in their lives.…”
Section: Researchmentioning
confidence: 66%
“…Family, namely parents, are commonly noted as the most influential people in the development and understanding of a person's racial identity, as they are the primary providers of information and answers to their children's questions concerning race (Brody et al, 2006;Bynum et al, 2007;Fischer & Shaw, 1999;Gillem, Cohn, & Throne, 2001;Hughes et al, 2006;Kerwin et al, 1993;Kerwin & Ponterotto, 1995;McClain DaCosta, 2004;Miville et al, 2005;O'Brien Caughy, 2004;Phillips Smith, & Johnson, 2009;Robbins et al, 2007;Rodriguez, Umaña-Taylor, Smalls, 2010;Root, 1998;Stevenson & Renard, 1993;White-Johnson et al, 2010;Wills et al, 2007).…”
Section: Factors Influencing Mixed Race Identity Developmentmentioning
confidence: 99%
“…É visto na literatura que em virtude de um passado de opressão e submissão social, o racismo reflete a realidade do acúmulo de estressores crônicos que se somam à cotidianidade da vida da população minoritária, a qual, frequentemente, traz estressores agudos e especialmente particularizados em contextos discriminatórios (Bynum et al, 2007;Clark et al, 1999;Whaley, 1998). Dito de outra forma, a vulnerabilidade das minorias raciais é também compreendida sob a luz do acúmulo de estressores e, com isso, o estresse é colocado como um fator explicativo para o impacto do racismo sobre a saúde (Caldwell et al, 2006;Franklin-Jackson & Carter, 2007;Schnittker & McLeod, 2005).…”
Section: Racismo E Saúde: Achados a Partir Da Teoria Do Estresseunclassified
“…Contrariando a expectativa da equidade dos fatores de proteção ou risco à saúde, uma constante na dimensão de vida e morte das populações é a evidente disparidade das condições de saúde entre os diversos estratos sociais, a saber: membros de grupos minoritários possuem maior probabilidade de nascerem em ambientes socialmente desfavorecidos (Cardoso, Santos, & Coimbra Júnior, 2005;Giscombé & Lobel, 2005), apresentarem maiores dificuldades no seu desenvolvimento físico e psíquico (Bynum, Burton, & Best, 2007;Caldwell, Guthrie, & Jackson, 2006) e vivenciarem intensamente a cronicidade de estressores sociais (Franklin & Boyd-Franklin, 2000;Harrell, 2000;Lopes, 2005).…”
unclassified
“…It involves the development and reinforcement of racial and cultural pride. As a positive coping strategy that raises self-esteem, racial socialization allows African Americans to better handle racist experiences (Bynum et al, 2007;Neblett et al, 2006) by acting as a buffer to the negative impact of racial discrimination.…”
Section: Racial Socializationmentioning
confidence: 99%